MANAGEMENT INFORMATION SYSTEM DEVELOPMENT STRATEGY TO SUPPORT DIGITAL TRANSFORMATION IN BUSINESS ORGANIZATIONS - Rikeniateni; Ryan Fahlevi; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Digital transformation has become a critical necessity for business organizations in the era of Industry 4.0. Rapid technological advances require companies to adopt management information systems (MIS) that support operational efficiency, data-driven decision-making, and enhanced competitiveness. This study aims to examine effective strategies for developing management information systems that align with digital transformation efforts in business organizations. The research employs a literature review and case study analysis across various industry sectors. The findings indicate that the successful development of MIS is strongly influenced by digital leadership, top management involvement, adaptive technology integration, and the enhancement of human resource competencies in information technology. This study recommends strategic approaches including the alignment of business goals with IT capabilities, implementation of flexible system architecture, and continuous performance evaluation of the system. These findings are expected to serve as a reference for organizations seeking to develop MIS as part of their digital transformation strategy.